Solar Lighting for the Base of the Pyramid : Overview of an Emerging Market - International Finance Corporation; World Bank (World Bank, Washington, DC, 2017)
This report presents an overview of current and projected market trends for off-grid lighting. It was commissioned and coordinated by Lighting Africa,a joint initiative from IFC and the World Bank.The report provides a snapshot of the off-grid lighting market and provides industry level data and analysis on key trends. It relies on the inputs ofa broad range of industry experts, manufacturers, distributors, scientists, marker researchers, and NGO leaders worldwide who contributed theirviews, time, and advice to the preparation of this document. This included interviews with over 70 solar market players in 10 African markets, anda range of lighting product manufacturers worldwide. The report will be updated every two years. A key component of the Lighting Africa landscape is the market for solar portable lights, which covers a range of lighting needs from individual tasks to general household lighting. This report presents a snapshot of this market and provides industry-level data and analysis on key trends. Excerpts from this report were used to establish a common foundation for the discussions at the Lighting Africa conference on May 18-20, 2010, and the full document is designed to be a reference point for futurefact-based analysis of the market opportunities for off-grid lighting. It should be noted that Lighting Africa is technology-neutral, but has assembled this report with a focus on solar-based lighting products, as this is a dominant and fast-growing sector of the off-grid space deserving lighting industry, donor, and private sector investor attention. The report relies on the input of a broad range of industry experts, manufacturers, distributors, and NGOs, including interviews with over 70 solar market players in 10 African markets and a dozen lighting product manufacturers worldwide. It will be updated every two years. We welcome your feedback and support in thiseffort and encourage you to reach out to the Lighting Africa team with your questions and feedback.